Investigation of 1, 3, 4 Oxadiazole Derivative in PTZ-Induced Neurodegeneration: A Simulation and Molecular Approach - Faheem M; Althobaiti YS; Khan AW; Ullah A; Ali SH; Ilyas U (Dove Medical Press, 2021)
Muhammad Faheem,1 Yusuf S Althobaiti,2,3 Abdul Waheed Khan,4 Aman Ullah,1 Syed Hussain Ali,1 Umair Ilyas1 1Riphah Institute of Pharmaceutical Sciences, Riphah International University, Islamabad, Pakistan; 2Department of Pharmacology and Toxicology, College of Pharmacy, Taif University, Taif, 21944, Saudi Arabia; 3Addiction and Neuroscience Research Unit, Taif University, Taif, 21944, Saudi Arabia; 4Department of Pharmacy, The University of Lahore, Islamabad, PakistanCorrespondence: Muhammad Faheem; Yusuf S Althobaiti Email muhammad.faheem@riphah.edu.pk; althobaiti@tu.edu.saObjective: The study investigated the effect 5-[(naphthalen-2-yloxy) methyl]-1,3,4-oxadiaszole2-thiol (B3) in animal model of acute epileptic shock.Methods: The pharmacokinetics profile of B3 was checked through SwissADME software. The binding affinities of B3, diazepam, and flumazenil (FLZ) were obtained through Auto Dock and PyRx. Post docking analysis and interpretation of hydrogen bonds were performed through Discovery Studio Visualizer 2016. Molecular dynamics simulations of three complexes were carried out through Desmond software package. B3 was then proceeded in PTZ-induced acute seizures models. Flumazenil was used in animal studies for elucidation of possible mechanism of B3. After behavioral studies, the animals were sacrificed, and the brain samples were isolated and stored in 4% formalin for molecular investigations including H and E staining, IHC staining and Elisa etc.Results: The results demonstrate that B3 at 20 and 40 mg/kg prolonged the onset time of generalized seizures. B3 considerably increased the expression of protective glutathione S-transferase and glutathione reductase and reduced lipid peroxidation and inducible nitric oxide synthase (P < 0.001) in the cortex. B3 significantly suppressed (P < 0.01) the over expression of the inflammatory mediator tumor necrosis factor-α, whose up-regulation is reported in acute epileptic shocks.Conclusion: Hence, it is concluded from the aforementioned results that B3 provides neuroprotective effects PTZ-induced acute epileptic model. FLZ pretreatment resulted in inhibition of the anticonvulsant effect of B3. B3 possesses anticonvulsant effect which may be mediated through GABAA mediated antiepileptic pathway.Keywords: docking, molecular dynamic simulations, gamma amino butyric acid A